(untitled) (MCIT: Proceedings of International scientific and practical conference, 2020)
The article analyses the connection between the clients’ reviews of the texts and their published ratings. To realize the task the language R and the packages such as jsonlite, tm, SnowballC, wordcloud, RColorBrewer, ggplot2 and others have been chosen. We used the data of the service Yelp, opened for academic goals and analysis [6]. For the analysis we used sentiment analysis. Sentiment analysis is the computational treatment of opinions, sentiments and subjectivity of text.